Synthesis of Flower-Like g-C3N4/BiOBr and Enhancement of the Activity for the Degradation of Bisphenol A Under Visible Light Irradiation - Wu, Jun; Xie, Yu; Ling, Yun; Dong, Yunyun; Li, Jian; Li, Shiqian; Zhao, Jinsheng (Frontiers in Chemistry, 2019)
The high recombination rates of photogenerated electron-holes inhibit greatly the catalytic activity of semiconductor photocatalyst. Herein, the heterojunctions of flower-like g-C3N4/BiOBrcomposites were synthesized as photocatalysts by a simple hydrothermal process. The X-ray diffraction, scanning electron microscopy and X-ray photoelectron spectrometer were utilized to characterize the sample's structure and light absorption properties. The results demonstrated that BiOBr-g-C3N4-4:1 showed excellent photocatalytic properties and 96.6% of bisphenol (BPA) was removed in 120 min with illumination of visible light due to its narrower band gap than that of pure BiOBr. BiOBr offer little electrons during the photocatalytic reaction. Moreover, the heterostructure between BiOBr and g-C3N4 facilitates the separationsof photogenerated carries. Excellent stability was exhibited after five cyclic degradation of methyl orange (MO) with the illumination of visible light. The active species trapping experiment indicated that superoxide radical anions (O2•-) and hole (h+) have a great effect on the reaction. A possible mechanism was proposed to explain the whole process of photocatalytic reaction.